2016
DOI: 10.1002/2015gl067233
|View full text |Cite
|
Sign up to set email alerts
|

Combining AIRS and MLS observations for three‐dimensional gravity wave measurement

Abstract: Gravity waves play a critical role in transporting energy and momentum between the troposphere, stratosphere, and mesosphere. Satellite measurements provide a powerful tool to investigate these waves across the globe. However, many present methods cannot yield reliable estimates of wave momentum fluxes or the directions of these fluxes. Here we present a new method which addresses this problem by combining observations from Atmospheric Infrared Sounder (AIRS) and Microwave Limb Sounder (MLS) in three dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 53 publications
8
55
0
Order By: Relevance
“…Wright et al (2011) compared HIRDLS, COSMIC, and SABER detections of stratospheric gravity waves during the years 2006-2007 and concluded that, when allowing for their different vertical resolution capabilities, the three instruments reproduce each other's results for magnitude and vertical scale of perturbations to within their resolution limits in approximately 50 % of the cases. In a second study (Wright et al, 2016a) investigated whether the dissimilar results of many gravity wave studies are primarily of instrumental or methodological origin. Their analysis is located around the southern Andes and Drake Passage with different gravity-wave-resolving instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Wright et al (2011) compared HIRDLS, COSMIC, and SABER detections of stratospheric gravity waves during the years 2006-2007 and concluded that, when allowing for their different vertical resolution capabilities, the three instruments reproduce each other's results for magnitude and vertical scale of perturbations to within their resolution limits in approximately 50 % of the cases. In a second study (Wright et al, 2016a) investigated whether the dissimilar results of many gravity wave studies are primarily of instrumental or methodological origin. Their analysis is located around the southern Andes and Drake Passage with different gravity-wave-resolving instruments.…”
Section: Discussionmentioning
confidence: 99%
“…At this level, in the DJF season, the OGWD is dominated by a Himalayan hotspot, which has not received significant attention in observational analyses yet (probably due to its emergence at rather lower levels). However, enhanced momentum fluxes have already been observed in this region, e.g., by Wright et al (2016a). Another hotspot emerging in the Northern Hemisphere (NH) is connected with the Rocky Mountains.…”
Section: Cmam-sd Gwd Climatologymentioning
confidence: 99%
“…Figure 1 shows the OGWD climatology at 100, 50, 30 and 10 hPa levels. The 100 hPa level is traditionally below the level taken into account in the GW analyses from satellite observations (e.g., Šácha et al, 2015;Wright et al, 2016a). At this level, in the DJF season, the OGWD is dominated by a Himalayan hotspot, which has not received significant attention in observational analyses yet (probably due to its emergence at rather lower levels).…”
Section: Cmam-sd Gwd Climatologymentioning
confidence: 99%
“…Pre-smoothing granules so as to exclude these perturbations (Wright et al, , 2016b) is one solution. Excluding even more wavenumber voices corresponding to short horizontal wavelengths from our 2DST analysis is another solution.…”
Section: Small-scale Perturbations and The Attenuation Correctionmentioning
confidence: 99%